2009
DOI: 10.4028/www.scientific.net/msf.631-632.253
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing of Functionally Graded Porous Products by Selective Laser Sintering

Abstract: Selective laser sintering (SLS) is a rapid prototyping technique which is used to manufacture plastic and metal models. The porosity of the final product obtained by SLS can be controlled by changing the energy density level used during the manufacturing process. The energy density level is itself dependent upon manufacturing parameters such as laser power, hatching distance and scanning speed. Through mechanical characterization techniques, it is possible to quantitatively relate the energy density levels to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Besides, the LPBF process has been employed in medical applications for producing customized bioimplants [53][54][55]. Recently, new materials, including metal matrix nanocomposites (MMNCs) [56][57][58] and functionally graded materials (FGMs) [59][60][61], are developed through the LPBF technology.…”
Section: Laser Powder Bed Fusionmentioning
confidence: 99%
“…Besides, the LPBF process has been employed in medical applications for producing customized bioimplants [53][54][55]. Recently, new materials, including metal matrix nanocomposites (MMNCs) [56][57][58] and functionally graded materials (FGMs) [59][60][61], are developed through the LPBF technology.…”
Section: Laser Powder Bed Fusionmentioning
confidence: 99%
“…91 Process parameter is formed by varying the manufacturing parameters to obtain variable energy densities. 97 Energy density is the ratio of power and beam section. 98 From equation (1) 5,21 by controlling the laser power, scanning speed, hatching speed and layer thickness, the FGM characteristics could be formed…”
Section: Design Of Glsmentioning
confidence: 99%
“…Therefore, DLS is a potential technique to manufacture porous materials. Erdal et al (2010) showed clearly that the porosity of the structure obtained by DLS could be changed by varying laser energy input and liquid phase content. However, as Agarwala et al (1995) pointed out, high-porosity sintered part could not be obtained by this way because of low strength of such samples.…”
Section: Introductionmentioning
confidence: 97%